The anti-apprenticeship of observation: How negative prior language learning experience influences English language teachers' beliefs and practices. (August 2016) - Moodie, Ian
Abstract: This study problematizes an issue for language teacher development in foreign language contexts by investigating the prior language learning experiences of South Korean English teachers and the influence of that experience on their teaching beliefs and practices. Across a generation, teachers had to adapt from a structural to a communicative-oriented curriculum. Prior research has shown that trainees lacking experience with communicative language teaching as students are less likely to teach communicatively; however, little attention has been paid to this issue locally. In the inquiry, data were collected from reflective writing with 18 in-service English teachers and follow-up interviews with 4 participants (2 novice and 2 experienced teachers). Findings from a grounded theory analysis show that participants' public school English learning experience served as an anti-apprenticeship of observation ; that is, their own public school teachers provided models of what not to do as language teachers. Therefore, an implication of this study is that teacher education must play an important role in transmitting the professional discourse and having trainees critically reflect on their prior learning experience. Reflective inquiry is rare in this context; however, this paucity of reflective practice creates an opportunity for researchers to provide an empirical contribution regarding its efficacy.